Haplotype and phylogenetic diversity using mitochondrial 12S rRNA gene marker in Bali cattle - T. Suselowati; R. R. Noor; J. Jakaria (Journal of the Indonesian Tropical Animal Agriculture, 2023)
Bali cattle is one of Indonesia's original livestock genetic resources. The 12S rRNA can be used as a marker of genetic diversity, and until now, there has been no report on Bali cattle. The study was aimed to analyze the gene of mtDNA 12S rRNA to determine haplotype diversity and phylogenetics in Bali cattle populations of the eastern region of Indonesia. A total of 95 blood samples used consisted of three different populations which were Bali cattle, Ongole crossbred (PO) and Madura cattle as a comparison. This research was analyzed using PCR and sequencing methods. The data were analyzed using the cluster W method for estimating genetic distances, calculating diversity, and reconstructing phylogenetic trees using the MEGAX, DNAsP and Network. The genetic distance values ranged from 0.00200 to 0.01508, and the Haplotype diversity values ranged from 0.66000 to 0.91111. The nucleo-tide diversity values ranged from 0.00174 to 0.01673. There were 16 haplotypes found. The values of Gst, Nst and Fst were 0.00803, 0.07550, 0.07622; respectively. Based on the analysis, there were dif-ferences between Bali cattle from various populations, there were specific haplotypes. The 12S rRNA gene can be used as a genetic marker for diversity studies in Bali cattle and other cattle breeds although the diversity is low.